1 Diplomasi Pertahanan Indonesia dalam Membangun Identitas Berbeda di antara Negara- Negara di Kawasan Asia Tenggara - Prayoga, Adhit (Jurnal Diplomasi Pertahanan, 2020)
The country acts based on its political identity, where several elements like interactions,norms, culture, status, and state history are able to form this identity. Every country hasa different way to understand its element, which generates different identities, policies,and strategies between countries in the international system. The purpose of this studyis to explain the accumulation of identity-forming elements that form the identity of freeand active foreign policy in Indonesia. This research was prepared using the perspectiveof Constructivism, the theory of Free and Active Politics as well as Defense Diplomacy.This research used descriptive qualitative research methods in which the research datawas obtained through a literature review. The results of this research indicate thatIndonesia, through an understanding of the elements forming identity, has formed a freeand active foreign policy identity. Indonesia uses free and active identity to achievenational interests and maintain its existence in the international system. With a differentpolitical identity from Indonesia, other countries in Southeast Asia tend to cooperatewith either the United States of America or China. Through the implementation of freeand active foreign policy, Indonesia is the only neutral country in Southeast Asia whichmeans that Indonesia is in the middle of both superpowers.Keywords: Political Identity; Free and Active; National Interest; Tendency; andNeutrality